Phosphorylation of USP33 by CDK1 stabilizes the mTORC2 component SIN1 - Yalei Wen; Caishi Zhang; Mingchao Liang; Xiao Yang; Hu Zeng; Rui Wan; Xiuqing Ma; Lei Huang; Mei Li; Qiushi Zhang; Liheng Li; Shengying Qin; et al. (Cell Death and Disease)
Abstract Understanding the mechanisms underlying chemoresistance is critical for improving cancer therapies. SIN1 plays a pivotal role in maintaining mTORC2 integrity and activation, which regulates key cellular processes. In this study, we demonstrate that elevated SIN1 expression in pancreatic ductal adenocarcinoma (PDAC) correlates with poor patient survival outcomes. Conversely, SIN1 deletion reduces tumor growth and enhances PDAC sensitivity to chemotherapy. We identify USP33 as a bona fide deubiquitanase of SIN1, essential for its stabilization in PDAC. This stabilization promotes chemoresistance by activating the mTORC2-AKT pathway. Additionally, we show that CDK1 directly phosphorylates USP33, enhancing its deubiquitinase activity toward SIN1 and driving PDAC progression. Inhibition or genetic ablation of CDK1 significantly diminishes these malignant phenotypes. Furthermore, we observe a strong positive correlation between CDK1, USP33, and SIN1 expressions in PDAC tissues. Our results provide compelling preclinical evidence that targeting the CDK1–USP33 axis may offer a promising therapeutic strategy to destabilize SIN1 and overcome chemoresistance in PDAC and potentially other aggressive cancers.